Effect of Gemfibrozil, Rifampicin, or Probenecid on the Pharmacokinetics of the SGLT2 Inhibitor Empagliflozin in Healthy Volunteers - Macha, Sreeraj; Koenen, Rüdiger; Sennewald, Regina; Schöne, Katja; Hummel, Noemi; Riedmaier, Stephan; Woerle, Hans J.; Salsali, Afshin; Broedl, Uli C. (Clinical therapeutics, 2014)
Empagliflozin is a potent, oral, selective inhibitor of sodium glucose cotransporter 2 in development for the treatment of type 2 diabetes mellitus. The goal of these studies was to investigate potential drug–drug interactions between empagliflozin and gemfibrozil (an organic anion-transporting polypeptide 1B1 [OATP1B1]/1B3 and organic anion transporter 3 [OAT3] inhibitor), rifampicin (an OATP1B1/1B3 inhibitor), or probenecid (an OAT3 and uridine diphosphate glucuronosyltransferase inhibitor). Two open-label, randomized, crossover studies were undertaken in healthy subjects. In the first study, 18 subjects received the following in 1 of 2 randomized treatment sequences: a single dose of empagliflozin 25 mg alone and gemfibrozil 600 mg BID for 5 days with a single dose of empagliflozin 25 mg on the third day. In the second study, 18 subjects received a single dose of empagliflozin 10 mg, a single dose of empagliflozin 10 mg coadministered with a single dose of rifampicin 600 mg, and probenecid 500 mg BID for 4 days with a single dose of empagliflozin 10 mg on the second day in 1 of 6 randomized treatment sequences. In the gemfibrozil study, 11 subjects were male, mean age was 35.1years and mean body mass index (BMI) was 23.47kg/m2. In the rifampicin/probenecid study, 10 subjects were male, mean age was 32.7years and mean BMI was 23.03kg/m2. Exposure to empagliflozin was increased by coadministration with gemfibrozil (AUC0–∞: geometric mean ratio [GMR], 158.50% [90% CI, 151.77–165.53]; Cmax: GMR, 115.00% [90% CI, 106.15–124.59]), rifampicin (AUC0–∞: GMR, 135.20% [90% CI, 129.58–141.06]; Cmax: GMR, 175.14% [90% CI, 160.14–191.56]), and probenecid (AUC0–∞: GMR, 153.47% [90% CI, 146.41–160.88]; Cmax: GMR, 125.60% [90% CI, 113.67–138.78]). All treatments were well tolerated. Increases in empagliflozin exposure were <2-fold, indicating that the inhibition of the OATP1B1/1B3, OAT3 transporter, and uridine diphosphate glucuronosyltransferases did not have a clinically relevant effect on empagliflozin exposure. No dose adjustments of empagliflozin were necessary when it was coadministered with gemfibrozil, rifampicin, or probenecid. ClinicalTrials.gov identifiers: NCT01301742 and NCT01634100.